Debating the War in Ukraine Counterfactual Histories and Future Possibilities - Forsberg, Tuomas (Taylor & Francis, 2023)
Debating the War in Ukraine discusses whether the war could have been avoided, and, if so, how? In this dialogical book, the authors discuss nodal points of history in terms of counterfactuals and contrastive explanations, concluding by considering future possibilities. They start in the 1990s where several causal elements of the war originate involving Russia's economic developments and Europe's security arrangements. Moving on to the next decade, they focus on the Iraq war, colour revolutions, and NATO's 2008 announcement that Ukraine and Georgia will become members. Finally, they explore the past decade including the Ukrainian crisis of 2013-2014, the annexation of Crimea, and the consecutive war in east Ukraine. The current war can also be seen as a continuum of that war. The authors agree that NATO's 2008 announcement on Ukraine's and Georgia's NATO membership was an unnecessary provocation, and that the implementation of the Minsk agreement could have prevented the current war, but otherwise their analysis of counterfactual possibilities differs, especially when it comes to the action-possibilities of the West (including diverse actors). These differences are not just dependent on different readings of relevant evidence but, importantly, stem from dissimilar contrast spaces and divergent theoretical understandings of the nature of states and mechanisms of international relations and political economy. This short, highly accessible book will be of great interest to all those studying and working in international relations and its various subfields such as peace and conflict studies and security studies, as well as all those wishing to understand more about the backdrop of Russia's invasion of Ukraine in February 2022. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. The Open Access version of this book was funded by University of Helsinki Library.